A study of interpersonal conflict and gender in classic and contemporary Malay films / Faridah Jaafar - Jaafar, Faridah (2013)
Conflicts, characterized by mistrust, suspicion, tension and hostility between individuals, groups or even nations are inevitable and inherent in human communication. Forms, causes, duration, outcomes, and effects of the conflicts which may not always be destructive vary but it is up to the disputants’ wisdom to deal with them to achieve amicable solutions. This thesis aimed to unveil interpersonal conflicts that disrupt interpersonal communication in the Malay society. It hoped to unveil the disputants, types, motives of conflicts and the way they dealt with the arising issues. The inclusion of gender was to establish an understanding of the types and degree of conflicts between Malay men and women and those of the same gender. It would be worthwhile to also investigate if interracial conflict was apparent. Gender issues in relation to inequality and power inequity were also embodied as part of the study. As real conflicts are difficult to capture, two sets of 19 classic and the contemporary Malay films were deployed. In order for the two conflict taxanomies to be established, Spradley’s illustrated in Kalbfleisch (1993) conflict model was consulted as it is important to know what types of conflicts emerge when one is caught in a difficult situation with another party. Some modifications were made to suit the context.\ Amartya Sen’s (2001) gender inequality model was then applied to examine the gender issues. The results include two conflict taxonomies representing the two eras revealing both similarities and differences. The majority of the conflicts portrayed are of the destructive issues and that both the genders do contribute to the disputes in the Malay society; the highest being between family members and Malay men are shown to be the biggest perpetrators of conflicts in interpersonal communication in the two eras. Malay women do face discrimination and inequality although they are bold and daring enough to make themselves heard and they fight for their rights. Interracial conflicts are shown to occur merely at work or professional levels involving more males than females. There is however a gradual move towards constructive conflict resolutions.